Ecologia del Lupo (Canis lupus) in Provincia di Genova: distribuzione, consistenza, alimentazione e impatto sulla zootecnia - Laura Schenone; Claudio Aristarchi; Alberto Meriggi (Hystrix, the Italian Journal of Mammalogy, 2005)
Abstract
Wolf Canis lupus ecology in Genoa province (northern Italy): species range, population, diet, and impact on livestock breeding From 1998 to 2003 we monitored the wolf population of Genoa province (Northern Italy) to define its range and number, and to know the feeding habits of the species and the predation impact upon animal husbandry. By recording and mapping all the presence signs (sightings, howling, predations, tracks, scats) on a transect net covering the province above 600 m a.s.l. we defined a species range partially overlapping the Aveto Regional Park, with an area of greater attendance corresponding to the M. Aiona-M. Penna massif, whereas in the remaining part of the province, already occupied in the previous years, the species was occasionally present. By snow tracking resulted that a small pack (2-5 individuals) was stable in the northeastern part of the province. The analysis of 190 scat samples, collected from 1998 to 2002, evidenced a diet based on three main food categories: livestock (56.8% as mean percent volume), wild ungulates (20.7%), and other vertebrates (11.5%). From 1996 to 2003, 95 claims for wolf predation on livestock (69.5% sheep, 28.4% goats, 1.0% cattle, 1.0% horses) were addressed to the Wildlife Service of the Genoa province, and 45 of these were paid after verification. In 2002 the Wildlife Service of Genoa province and the Aveto Regional Park signed a protocol aimed to the safeguard of the wolf population and of the local animal husbandry.
Riassunto
Dal 1998 al 2003 è stato effettuato un monitoraggio della popolazione di Lupo (Canis lupus) in provincia di Genova, volto a definirne la distribuzione e la consistenza, nonché le abitudini alimentari e l'impatto sulla zootecnia. Attraverso la raccolta e la mappatura dei segni di presenza è stato definito un areale in parte corrispondente al Parco naturale regionale dell'Aveto, con una zona di maggiore frequentazione, stabile negli anni e coincidente col gruppo del M. Aiona - M. Penna, mentre nel resto della provincia e nelle aree occupate dalla specie negli anni precedenti, la presenza è risultata occasionale. Utilizzando il metodo del conteggio delle tracce su neve (snow tracking), sono stati effettuati censimenti annuali dai quali è risultato che un piccolo nucleo di lupi (da 2 a 5), probabilmente un gruppo familiare, ha frequentato stabilmente, nel periodo di studio, la parte nord-orientale del territorio provinciale. L'analisi di 190 campioni di feci, raccolte dal 1998 al 2002, ha evidenziato come la dieta fosse basata principalmente su tre categorie alimentari: ungulati domestici (56,8% in volume medio percentuale), ungulati selvatici (20,7%), altri vertebrati (11,5%). Dal 1996 al 2003 sono pervenute all'Amministrazione provinciale di Genova 95 denunce di predazione (capi denunciati come uccisi, feriti o dispersi); di queste, 45 (47,4%) sono state risarcite in seguito ad accertamento tecnico. Nel 2002, l'Amministrazione provinciale di Genova e il Parco dell'Aveto hanno sottoscritto un protocollo d'intesa finalizzato a tutelare, nell'area del Parco, il Lupo e gli allevamenti locali.